Development of snakes and ladders game (disaster response) as earthquake mitigation for children - Besse Nirmala; Andi Agusniatih; Haerul Annuar (Universitas Ahmad Dahlan, 2020)
This study aims to produce of snakes and ladders game with feasible to increase understanding of children related to earthquake disaster mitigation. Snakes and ladders game will be applied to children aged 5-6 years in Palu city. This research is a research and development according to Borg and Gall. Data collection techniques using observation, interviews and questionnaries. Data analysis in the form of quantitative descriptive. The results showed that the assessment of the material validators get an average of 3.63, media validators get an average of 3.8, and disaster validators get an average of 3.75 (feasible category). In the initial field trials, it averaged persentage 78% and was included in the feasible category. Operational field trials get an average persentage of 87% included in the feasible category. Comparative study results obtained sig. (2-tailed) of 0,000 <0.05, it can be concluded that Ha is accepted, which means that